AMELIORATION OF WEANING STRESS IN CROSSBRED PIGLETS USING PREBIOTIC AND PROBIOTIC SUPPLEMENT (Indian Journal of Animal Production and Management, 2015)
The present study was designed to assess the effect of probiotic and probiotic on growth performance and variation on haematological profile of crossbred weaned pigs. A total of 20 weaned crossbred piglets of 87.5 percent Khasi local x Hampshire and Ghungroo of ten each were selected on the basis of weight and divided equally as into two groups irrespective of their sex. The feed additive had been added at the level of 2% in treatment group along with feed for three months during winter season. Individual body weight was measured at fifteen days interval and blood samples were collected at monthly intervals for haematological parameters. The final body weight at the end of the experiment was found to be 27.67 ± 5.36 kg in control group and 29.40 ± 2.22 kg in the treatment group. There was no significant difference in body weight between the treatment and the control groups at any stage of the experiment. There was significant (P
Keywords: Prebiotic; probiotic; Saccharomyces cervisiae; piglet; haematological parameter